Integration of MARKAS and ARKAS Application in BOS Fund Budget Management at the Elementary School Level, West Sumbawa Regency - Indra, Arjuna; Suparman, Suparman; Najamuddin, Najamuddin (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research discusses the implementation of the integration of the MARKAS and ARKAS applications in managing the BOS fund budget at the elementary school level in West Sumbawa Regency. The objectives of this research consist of: 1. To explain the system and procedures for implementing the integration of the MARKAS and ARKAS applications in managing the BOS fund budget at the elementary school level in West Sumbawa Regency. 2. To explain the benefits that can be felt in implementing the integration of the MARKAS and ARKAS applications in managing the BOS fund budget at the elementary school level in West Sumbawa Regency. 3. To determine the obstacles in implementing the integration of the MARKAS and ARKAS applications in managing the BOS fund budget at the elementary school level in West Sumbawa district. The research method used is a qualitative research design. Qualitative research is research that uses a scientific background, with the aim of interpreting phenomena that occur and is carried out by involving various existing methods. The number of informants used was 7 people from the District BOS Team and the school BOS Team in West Sumbawa Regency. Data collection procedures use observation, interviews and documentation. Data analysis uses qualitative descriptive analysis. The results of this research show that in terms of implementation it has been carried out well, increasing the effectiveness of data input in one input, increasing efficiency through automation which speeds up the administrative process, increasing accountability according to regulations and standards, and increasing transparency. So it can be concluded that the benefit of this system integration is improving the flow of information within an organization. It is hoped that the data recapitulation process and accountability for budget management of BOS funds in educational units can be well integrated nationally.